Green Synthesis of ZnO Nanoparticles using Piper chaudocanum L. Leaf Extract: Characterization and its Application in Pb (II) Adsorption - Thao, Truong Thi; Tam, Khieu Thi; Thom, Nguyen Thi Huong; Tuan, Nguyen Thuong (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5275, 2022)
In this study, Zinc oxide nanoparticles (ZnO NPs) were green synthesized using  Piper chaudocanum L. ( PC ) leaf extract by sol-gel method and used as an adsorbent for the removal of Pb (II) ions from aqueous solution. The synthesized ZnO NPs were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), Ultraviolet - visible spectroscopy (UV-Vis) and Brunauer - Emmet - Teller (BET). The results revealed high purity and wurtzite hexagonal structure of ZnO NPs in the size range of 28-37 nm. The morphology of the ZnO NPs varies in different polycrystalline aggregates depending on the amount of extract used, from nanorods to NPs clusters with a BET surface area of 8.56 m 2 g -1 . Pb (II) ion adsorption was investigated at different pH, contact time, initial metal ion concentration, adsorbent dose and temperature. ZnO NPs were synthesized using 30 mL PC leaf extract (ZS30) is the best Pb (II) absorbent. The adsorption isotherm was well described by Langmuir (at low concentration of Pb (II)) and Freundlich isotherm model (at higher concentration of Pb (II)). The adsorption process follows pseudo-second-order reaction kinetic with a high regression coefficient. The calculated thermodynamic parameters, ΔG o (between - 8.699 and - 7.569 kJ/mol at 298 - 316 K), ∆H o (-20.085 kJ/mol) showed that the adsorption of Pb (II) on ZS30 surface was feasible, spontaneous and exothermic, respectively. The first layer absorption is chemisorption while the next layers are physical adsorption.